Resource allocation for radar signal interception in ESM receivers - MacSween, Peter J. A. F (University of Ottawa (Canada), 2004)
Electronic Support Measures (ESM) receivers exist that are capable of detecting the transmissions from radar emitters in a robust and reliable manner. Typically, the receiver operator wishes to detect the transmitted signals from a known set of emitters as quickly as possible. To achieve this, a schedule is created that dictates the order in which the receiver will search for the various emitters. Techniques exist for predicting the maximum time to intercept between a receiver and an emitter, but they only work from known scheduling parameters. The quantity of emitters and the density of their signals typically prevents a naive approach to generating the schedule. The purpose of this thesis was to generate scanning receiver schedules that minimize the maximum time to intercept for a set of scanning emitters. Genetic algorithms and the use of pulse train theory were combined to generate the schedules in an automated fashion. The genetic algorithm consistently produced ESM receiver schedules that used duration values for each frequency band that were near the largest scan rate of all the emitters in each band. This was an unexpected result and demonstrated that the minimization of the maximum intercept time for a set of emitters can be accomplished using the maximum scan values. A new scheduling algorithm was created that utilized the maximum scan values. It generated ESM receiver schedules that were equivalent to the best schedules produced by the genetic algorithm scheduler, and produced them with much less computational effort.
Keywords: Engineering, Electronics and Electrical.